Soil stabilization with non-conventional eco-friendly agricultural waste materials: An experimental study. (March 2018) - Rahgozar, Mohammad Ali; Saberian, Mohammad; Li, Jie
Highlights: Provides a review on the previous research on application of Rice Husk Ash for soil stabilization. Presents an original and effective application of RAH. Soil stabilization with non-conventional ecofriendly agricultural waste materials. Provides a model for predicting properties of stabilized soil with RHA and cement. Abstract: Highway construction and maintenance are usually expensive, and cost control efficiency is imperative. Although there are several stabilization methods, soil stabilization with agricultural waste materials, such as rice husk ash (RHA), is among the most eco-friendly and affordable methods. The aim of this study is to experimentally investigate the effects of adding RHA and ordinary Portland cement on the geotechnical properties of the clayey sand sampled from the Sejzi area, which lies east of the city of Isfahan, Iran. First, the oxide compounds of RHA, cement, and soil were determined using the X-ray fluorescence (XRF) test. Five different compounds of the soil with 2, 4, 6, and 8% of cement were mixed, and, later, different percentages of RHA (0, 2, 4, 6, and 8%) were added to determine the unconfined compressive strength (UCS), California bearing ratio (CBR), optimum moisture content (ωopt ), and maximum dry density (γd ) of the stabilized soil compounds with 7, 14, and 28 curing days. The results showed that by increasing the content of RHA, the ωopt of the specimens increased, while the γd decreased. The 28-day-cured specimen with 6% RHA and 8% cement showed the highest values of UCS and CBR at 25.44 and 18.2 times more than those of the values for untreated soil, respectively. The scanning electron micrograph (SEM) test of the aforementioned stabilized soil was characterized as a well-structured soil matrix with very small pores, which can be attributed to the pozzolanic reactions of the cement and RHA. The effectiveness, abundance, and the low cost of RHA will attract considerable environmental interest in this research.